(untitled) (Ágora de Heterodoxias, 2018)
Since 2000 the Venezuelan territory has been affected by dry periods that caused a significant depletion in water reserves from large dams. The most important characteristics of mayor droughts that affected the water flows of 32 large reservoirs over the 1960-2005 period were evaluated. Standardized precipitation Index was used to measure the annual rainfall anomalies (SPI-12). The underlying pattern that configures the droughts in the space temporal context was identified by a cluster analysis. We have found that: a) dry periods are relatively frequent. They were alternated with wet periods; b) large reservoirs are gathered into eight geographic areas according to their exposure to droughts; c) droughts that affect the water flows can start or end suddenly or gradually in time.